2012
DOI: 10.1007/s10457-012-9495-7
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of afforestation on abandoned agriculture land in Latvia

Abstract: Abandonment of agriculture land and subsequent natural afforestation have been common features of the contemporary Latvian rural landscape, particularly in the period since 1990. This process affects the structure, ecology and visual qualities of the landscape. The study examines spatial characteristics of afforestation in relation to various environmental factors. The study was conducted in the central part of Latvia, where there is abundant abandoned agriculture land and a great variety of spatial afforestat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
0
7

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(45 citation statements)
references
References 51 publications
(68 reference statements)
3
35
0
7
Order By: Relevance
“…The inventory based on the remote sensing data showed that 81.9 % of the ''Forest'' (F) class was formed from arable land (A), 13.1 % from ''Pastures'' (P) and 5.0 % from ''Meadows'' (M). This confirms the problem commonly mentioned among the secondary forest succession on abandoned arable land where the agriculture has been stopped (WEZYK and DE KOK, 2005;BOWEN et al, 2007;OIKONOMAKIS and GANATSAS, 2012;RUSKULE et al, 2012;SUSYAN et al, 2011;ZHANG, 2005). The goal of the paper was to define the possibilities for detecting vegetation classes in an automatic way using ALS and the image data.…”
Section: Resultssupporting
confidence: 71%
“…The inventory based on the remote sensing data showed that 81.9 % of the ''Forest'' (F) class was formed from arable land (A), 13.1 % from ''Pastures'' (P) and 5.0 % from ''Meadows'' (M). This confirms the problem commonly mentioned among the secondary forest succession on abandoned arable land where the agriculture has been stopped (WEZYK and DE KOK, 2005;BOWEN et al, 2007;OIKONOMAKIS and GANATSAS, 2012;RUSKULE et al, 2012;SUSYAN et al, 2011;ZHANG, 2005). The goal of the paper was to define the possibilities for detecting vegetation classes in an automatic way using ALS and the image data.…”
Section: Resultssupporting
confidence: 71%
“…The lower sequestration rate of NS sites is probably attributable to the 20-year delay before natural succession establishment. Such delays have also been reported at higher and lower latitudes: 15-20 years in Latvia at ~57° N [34], 10-42 years in UK at ~54° N [35], and 20-55 years in the Mediterranean region at ~40° N [36,37]. The distance from the seed stand is probably not the main explanation, since wind dispersal of seeds can occur over much larger distances.…”
Section: Vegetationmentioning
confidence: 66%
“…For example, birch seeds can travel over 1 km in open terrain during winter [38]. Ruskule et al [34] rather suggest that, on rich soils, the development of a dense herbaceous vegetation cover can hinder the establishment of tree species. This explanation is consistent with the inhibition model of succession [39], and very likely applies to our study, since the soils were generally deep and well-drained, with a sandy to sandy loam texture, and host to a dense herbaceous plant cover on sites less than 20 years old.…”
Section: Vegetationmentioning
confidence: 99%
“…In this context, a good strategic planning and landscape design for bioenergy may provide an opportunity to move forward more sustainable production systems [84]. For example, Ruskule et al [85] showed that the spatial pattern of afforestation on abandoned agricultural land had an impact on the respective biodiversity outcome in Latvia. More importantly, energy crop production from marginal lands could directly compete with forage-livestock production.…”
Section: B2: Combination Of First-generation and Dedicated Energy Cromentioning
confidence: 99%